Accurate Differentiation of Streptococcus pneumoniae from other Species within the Streptococcus mitis Group by Peak Analysis Using MALDI-TOF MS - Marín, Mercedes; Cercenado, Emilia; Sánchez-Carrillo, Carlos; Ruiz, Adrián; Gómez González, Álvaro; Rodríguez-Sánchez, Belén; Bouza, Emilio (Frontiers in Microbiology, 2017)
Despite the benefits of MALDI-TOF MS technology (Matrix-Assisted Laser Desorption-Ionization Time-Of-Flight Mass Spectrometry) reported worldwide and the continuous improving of the available databases, discrimination between Streptococcus pneumoniae and closely related species within the Streptococcus mitis group (SMG) using this methodology has been suboptimal. However, the accurate identification at the species level of this group of microorganisms is important for the appropriate management of infected patients. In this study, 216 SMG isolates -101 S. pneumoniae and 115 corresponding to 7 non-pneumococcal species within this group- were analysed. All the isolates had been previously identified by conventional methods (optochin and bile solubility tests) and non-pneumococcal isolates were confirmed by sequence analysis (sodA and plys genes) when required. The isolates were also identified with the MALDI Biotyper 3.1 (Bruker Daltonics, Bremen, Germany) using an updated library containing 6903 Main Spectra Profiles (MSPs). All the analysed S. pneumoniae were correctly identified with MALDI-TOF MS at species level using the most updated database and all the non-pneumococcal SMG isolates were also identified at the group level. Several peaks (4964.32, 6888.90 and 9516.46 m/z) have been found to be specific of S. pneumoniae, whilst a different set of peaks have proved to be present only in S. mitis (6839.07 m/z) and S. oralis (5297.61, 5822.53 and 6839.07 m/z). Peak analysis allowed correct species assignment of 101/101 S. pneumoniae isolates (100%) and 102/105 S. mitis/oralis isolates (97.1%). Thus, the implementation of MALDI-TOF MS plus peak analysis for the identification of this group of microorganisms may provide precise species-level information that will allow the early implementation of directed antibiotic therapy.